The acute effects of analogy and explicit instruction on movement and performance. (September 2019) - Bobrownicki, Ray; MacPherson, Alan C.; Collins, Dave; Sproule, John
Abstract: Objectives: To date, research concerning analogy and explicit instruction has focused on motor learning (i.e., change or development over many learning trials) with limited attention directed toward acute performance considerations. Accordingly, the present study examined the short-term, differential effects of analogy and explicit instructions on motor control. Methods and design: Employing a within-subjects semi-counterbalanced design, 20 novice adult participants performed a dart-throwing task under baseline, analogy, and explicit instruction conditions. Across all throwing trials, movement and performance were evaluated using the dependent variables of throwing accuracy, elbow joint variability, angular velocity, and throw duration. Results: Analyses did not reveal any statistically significant differences between analogy and explicit instructions for any of the study's dependent measures. Compared to baseline performances, participants in both verbal instruction conditions demonstrated significantly less accuracy, significantly greater elbow joint variability, significantly slower angular velocity, and significantly longer throwing times. Conclusions: Findings suggest that verbal instruction may differentially affect performance in motor control situations, compared to motor learning contexts, leading to reduced accuracy; slower, more deliberate control; and increased levels of movement variability. Going forward, practitioners may need to more carefully consider not only how motor skills are instructed, but also the purpose and timing of any instructions. Highlights: When using analogy or explicit instructions in motor control contexts, participants did not exhibit any statistically significant differences. Compared to baseline, analogy and explicit instructions led to slower, less accurate throwing with more joint variability. Findings suggest that novices may have difficulty immediately implementing verbal instructions. Sport psychologists and other applied practitioners should carefully consider how, why, and when instructions are provided.